Komitmen hidup membiara atau hidup religius dalam perspektif komitmen organisasi - Maria Imakulata Tere; Ignasius Ledot (Jurnal Konseling dan Pendidikan, 2021)
Commitment is a promise or attachment to a particular object or subject and is related to the personal social aspect. In the context of religious life, the commitment of a religious person or who chooses to live as nun is a pledge of vows; purity, obedience and poverty. This research aims to see life commitment deepen in the perspective of organizational commitment according to Meyer and Allen. Respondents in this study were 14 junior sisters, those who were already in the relationship but still in formal assistance by formators or counselors. Qualitative research was used as a methode in this research. Of the three models of organizational commitment, affective commitment is a commitment that is in line with the commitment of religious life. The findings show that life commitment of the sisters, in the perspective of organizational commitment, is still in the process of growth towards affective commitment. The respondents need to be accompanied in order to grow towards affective commitment or commitment to religious life